Effects of Thymus vulgaris and Zingiber officinale Aqueous on Semen Parameters, Testes Weight and Histology Measurements of Broiler Breeder Male - Shanoon , A.K.; Jassim, Mahdi S. (International Journal of Poultry Science, 2012)
To examine the effect of Ginger rhizome and thyme leaf aqueous extract on male reproductive system and the mechanisms of these effects the aqueous were add two drinking water to two groups of male broilers breeder ROSS308, the addition start in 24wk and end in 44wks age at levels 5% and 10% for each plant aqueous where the other group was a control (received a distilled water). ejaculate volume, sperm concentration, counts, movements, motility, abnormality, testes weight and histology measurements were the mean characteristics studied. There were a significant increase (P<0.05) in ejaculate volume, sperm concentration, counts, movements and a significant decrease (P<0.05) in motility and abnormality, also there were a significant increase (P<0.05) in testes weight, percentage and histology measurements, there for my results refer to that extract of ginger and thyme conceder as pro-fertility properties in male broiler which might be a product of both its potent antioxidant properties and androgenic activities.